Eksplorasi Desain Batik Unesa Berbasis Kangkung Air: Keberlanjutan dan Representasi Identitas Visual Institusi - Arifiana, Deny; Nahari, Inty; Kharnolis, Mein (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
Batik, as an Indonesian cultural heritage, holds significant potential to support sustainable fashion, particularly through the exploration of nature-based motifs and the use of more environmentally responsible materials. However, its application as an institutional identity marker remains limited, especially in integrating sustainability values with the visual character of an institution. This study aims to develop a sustainable institutional batik design by adopting the stylization of water spinach (Ipomoea aquatica) as a symbol of ecological growth, combined with visual elements of Universitas Negeri Surabaya (Unesa). The Practice-Led Research method was employed across four stages: pre-design, design, realization, and presentation and evaluation. The study produced ten Unesa batik designs, from which three were selected as the best based on expert assessments using four criteria: functionality, cultural identity and expression, aesthetics, and creativity. The findings indicate that Batik Andaru Tirta UNESA effectively represents both the ecological character and institutional identity of the university. Future research may extend to material testing, the exploration of border motifs, and prototype refinement to support more sustainable production practices.